Alkali Cation Potential and Functionality in the Nanoporous Prussian Blue Analogues. (20th March 2013) - Moritomo, Yutaka; Tanaka, Hiroshi
Abstract : Cation and/or molecule transfer within nanoporous materials is utilized in lithium-ion secondary battery, ion exchange, hydrogen storage, molecular sensors, molecular filters, and so on. Here, we performed ab initio total energy calculation to derive the alkali cation potential in the Prussian blue analogues, A x M [ Fe ( CN ) 6 ] y z H 2 O (A = Li, Na, K, Rb, and Cs; M = Co, Ni, Mn, and Cd), with jungle-gym-type nanoporous framework. The potential curves of larger cations, that is, K +, Rb + and Cs +, exhibit a barrier at the window of the host framework, while those of the smaller cations, that is, Li + and Na +, exhibit no barrier. We will discuss the useful functionalities observed in the Prussian blue analogues, that is, (a) battery properties mediated by Li + intercalation/de-intercalation, (b) electrochromism mediated by Na + transfer in all solid device, and (c) the elimination of Cs + from aqueous solution by precipitation, in terms of the alkali cation potentials.